Heterologous expression and kinetic characterization of the α, β and αβ blend of the PPi-dependent phosphofructokinase from Citrus sinensis - Muchut, Robertino J (Plant science : an international journal of experimental plant biology, 2019)
Copyright © 2018 Elsevier B.V. All rights reserved.